Overview of the Use of Online Games in Grade XI Students at SMK N 2 Purwokerto - Rahayu, Sri; Triana, Noor Yunida; Wirakhmi, Ikit Netra (Universitas Ibn Khaldun Bogor, 2025)
The development of games in Indonesia is increasing rapidly along with the advancement of communication technology that drives the game industry. One of the most popular types of games is online games. Based on the results of the pre-survey obtained by the researcher on 15 students of SMK N 2 Purwokerto, there were students who played online games when they were free and after they performed the dzuhur prayer, 12 students said that every class must have someone who plays online games but not all children play online games at school, there are also those who mention playing online games when they are at home. The purpose of the study was to get an overview of the use of online games in grade XI students at SMK N 2 Purwokerto. This study uses a quantitative descriptive analysis method with a cross sectional approach in the form of a survey. This study involved 140 students who were taken using the total sampling technique. The instrument used was a questionnaire. The results of this study were obtained by the majority of respondents who were male (62.1%), the length of use of online games was mostly in the low category (67.1%), and the distribution of online game use in the medium category was as much as (61.2%). This shows that the use of online games in SMK N 2 Purwokerto students is in the medium category. It is hoped that the school will be able to hold a student guidance program regarding time management in playing online games.